Application of Modified Couple Stress Theory and Homotopy Perturbation Method in Investigation of Electromechanical Behaviors of Carbon Nanotubes (Advances in Applied Mathematics and Mechanics, 2018)
The paper presents the size-dependent behaviors of the carbon nanotubesunder electrostatic actuation using the modified couple stress theory and homotopyperturbation method. Due to the less accuracy of the classical elasticity theorems, themodified couple stress theory is applied in order to capture the size-dependent propertiesof the carbon nanotubes. Both of the static and dynamic behaviors under staticDC and step DC voltages are discussed. The effects of various dimensions and boundaryconditions on the deflection and pull-in voltages of the carbon nanotubes are to beinvestigated in detail via application of the homotopy perturbation method to solvethe nonlinear governing equations semi-analytically.